Distinct defects in early innate and late adaptive immune responses typify impaired fracture healing in diet-induced obesity - Khajuria, Deepak Kumar; Reider, Irene; Kamal, Fadia; Norbury, Christopher C.; Elbarbary, Reyad A. (Frontiers in Immunology, 2023)
Bone fractures, the most common musculoskeletal injuries, heal through three main phases: inflammatory, repair, and remodeling. Around 10% of fracture patients suffer from impaired healing that requires surgical intervention, a huge burden on the healthcare system. The rate of impaired healing increases with metabolic diseases such as obesity-associated hyperglycemia/type 2 diabetes (T2D), an increasing concern given the growing incidence of obesity/T2D. Immune cells play pivotal roles in fracture healing, and obesity/T2D is associated with defective immune-cell functions. However, there is a gap in knowledge regarding the stoichiometry of immune cells that populate the callus and how that population changes during different phases of healing. Here, we used complementary global and single-cell techniques to characterize the repertoire of immune cells in the fracture callus and to identify populations specifically enriched in the fracture callus relative to the unfractured bone or bone marrow. Our analyses identified two clear waves of immune-cell infiltration into the callus: the first wave occurs during the early inflammatory phase of fracture healing, while the second takes place during the late repair/early remodeling phase, which is consoistent with previous publications. Comprehensive analysis of each wave revealed that Iinnate immune cells were activated during the early inflammatory phase, but in later phases they returned to homeostatic numbers and activation levels. Of the innate immune cells, distinct subsets of activated dendritic cells were particularly enriched in the inflammatory healing hematoma. In contrast to innate cells, lymphocytes, including B and T cells, were enriched and activated in the callus primarily during the late repair phase. The Diet-Induced Obesity (DIO) mouse, an established model of obesityassociated hyperglycemia and insulin resistance, suffers from multiple healing defects. Our data demonstrate that DIO mice exhibit dysregulated innate immune responses during the inflammatory phase, and defects in all lymphocyte compartments during the late repair phase. Taken together, our data characterize, for the first time, immune populations that are enriched/activated in the callus during two distinct phases of fracture healing and identify defects in the healing-associated immune response in DIO mice, which will facilitate future development of immunomodulatory therapeutics for impaired fracture healing.